"Development with Social justice : Proceedings of the Seminar, held at NICD, Hyderabad 26-28 November, 1973/edited byV.R.K. Paramashamsa" - National Institute of Community Development (1973 Nov. 26-28 (Hyderabad, 1974)
This book deal with social justice
Keywords: Social Justice